AB0618 Patients' preferences for osteoporosis drug treatment: a discrete choice experiment. (23rd January 2014) - Hiligsmann, M.; Dellaert, B.; Dirksen, C.; van der Weijden, T.; Goemaere, S.; Reginster, J.-Y.; Watson, V.; Boonen, A.
Abstract : Background: The problem of medication non-adherence has emerged as a critical hurdle to osteoporosis management. With the recent introduction of new therapies with different administration schemes, understanding patients' preferences for osteoporosis medications may contribute to optimise treatment selection and to improve adherence to therapy. Objectives: This study aims to evaluate the preferences of osteoporotic patients for medication attributes, to establish how they trade between these attributes, and to estimate the willingness to pay for specific attributes. Methods: A discrete choice experiment was designed in which patients were asked to choose, for a series of hypothetical scenarios, between two unlabeled drug alternatives (and an opt-out option), which vary along several attributes of interest. Based on qualitative research with patients, drug treatment was described by five attributes: efficacy in reducing the risk of fracture, possible side-effects in 1 in every 50 patients, mode and frequency of administration and out-of-pocket contribution. This study employed a Bayesian efficient design to construct the 15 choice sets and a mixed logit panel data model estimate patients' preferences. Osteoporotic patients were recruited from 2 osteoporosis centres in Belgium and we also investigated whether high-risk patients (i.e. defined as FRAX-major risk greater than 10%) had different preferences than low-risk patients. Results: A total of 257 osteoporotic patients completed the experiment. Patients preferred a drug treatment with a higher risk reduction and a lower cost. They preferred oral monthly tablet and 6-month subcutaneous injection compared with weekly oral tablets, 3-month subcutaneous, and intravenous treatment every 3-month or yearly. Patients disliked more being at risk of gastro-intestinal disorders than at risk of skin reactions and flu-like symptoms. There was significant preference heterogeneity for all attributes except the subcutaneous injection ones. Respondents were willing on average to pay €16 per month or to trade 13.7% of drug's efficacy for oral monthly tablet or 6-month subcutaneous injection compared with other modes of administration. Patients with high-risk of fractures did not have significant differences in preferences compared with low-risk patients, except they placed higher value on, and are willing to pay more for, osteoporosis medications. Conclusions: This study revealed that, on the group level, osteoporotic patients had preferences for oral monthly tablet and 6-month subcutaneous injection, and disliked more gastro-intestinal disorders, and they are willing to trade efficacy or pay for such outcomes. Preference heterogeneity would suggest incorporating individual preferences into clinical/shared decision-making to improve osteoporosis care. Acknowledgements: This study was funded by Amgen Disclosure of Interest: None Declared